PENGATURAN DAN EFEKTIVITAS SANKSI PIDANA KORUPSI DALAM HUKUM POSITIF SERTA REFORMULASINYA DALAM PERSPEKTIF PEMBAHARUAN HUKUM PIDANA DI INDONESIA - Imam Fathwa; Siti Humulhaer; Bayu Triwibowo; Tri Susanto; Ratu Chumairoh Noor (Berajah Journal, 2026)
Corruption is one of the crimes that has serious impacts on the life of the nation and the state, as it causes state financial losses and hampers national development. Therefore, Indonesian positive law strictly regulates criminal sanctions against perpetrators of corruption through Law Number 31 of 1999 concerning the Eradication of Corruption Crimes as amended by Law Number 20 of 2001. This study aims to analyze the regulation of criminal sanctions for corruption in Indonesian positive law, evaluate the effectiveness of their implementation in judicial practice, and examine the reformulation of sentencing policies from the perspective of criminal law reform. The research method used in this study is normative legal research employing statutory and conceptual approaches. The results of the study indicate that the regulation of criminal sanctions for corruption in Indonesian positive law includes principal penalties in the form of imprisonment and fines, as well as additional penalties such as payment of compensation for state losses, asset confiscation, and revocation of certain rights. However, in practice, the implementation of these sanctions still faces several obstacles, including sentencing disparities and the suboptimal recovery of state financial losses. Therefore, it is necessary to reformulate criminal sanction policies for corruption through strengthening asset recovery mechanisms and establishing sentencing guidelines in order to realize a criminal justice system that is more effective, fair, and capable of creating a deterrent effect for perpetrators of corruption crimes.